(untitled) (Damu Journal of Sport Sciences, 2025)
The importance of the research lies in the use or implementation of specific exercises that vary in their performance and are expected to develop the skills of agility, motor balance, and dribbling in soccer. The research problem, through field observations and repeated observations of matches by players at a specialized school in Nasiriyah District, revealed a clear deficiency in the time coaches allocate to developing the skills of agility and motor balance. Neglecting to develop these two skills is a direct cause of players' weak ability to respond effectively to sudden situations during the match, which negatively impacts the accuracy of skill execution. The research objectives were to identify the effect of specific exercises on developing the skills of agility, motor balance, and dribbling in soccer players aged 11-12 years. The researcher used the experimental method using the two equivalent groups, control and experimental, to suit its suitability for solving the research problem. The researcher deliberately defined the research community, which is junior football players at the Specialized Football Center in Dhi Qar Governorate for the season (2023-2024), with (28) officially registered players. The researcher then selected his research sample, which numbered (20) players. One of the most important conclusions is that the qualitative exercises designed using a scientific method that is appropriate for the level of the sample and the nature of the game, and the aids used, contributed to the development of the characteristics of agility, motor balance, and dribbling skills, thus positively reflecting on the level of the members of the experimental group.